A systematic literature review on the use of multicriteria decision making methods for small and medium-sized enterprises innovation assessment - Rodríguez-Carrillo, Mayra Leticia; Pérez-Domínguez, Luis; Romero-López, Roberto; Luviano-Cruz, David; León-Castro, Ernesto (Frontiers in Artificial Intelligence, 2025)
Multi-criteria decision making (MCDM) methods are essential tools for assessing multiple factors in various contexts, including innovation in small and medium-sized enterprises (SMEs). In this study, a systematic literature review (SLR) was conducted based on a literature search in Web of Science, Scopus and Google Scholar, covering the period 2018–2024, taking as a basis the general guidelines and main phases of an SLR, in addition, the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) method was used, which allowed the selection of 25 relevant articles. From the analysis, four main trends in innovation assessment were identified: Innovation Capacity and Business Strategies, Open Innovation, Evaluation and Management, Technological and Digital Innovation, and Green Innovation and Sustainability. The results indicate that India and China are the countries with the highest volume of publications on this topic, while the business and academic sectors are the most studied, followed by the social sector. In addition, other key factors assessed in SMEs using MCDM methods were identified, grouped into five main themes including industry 4.0 and digital transformation, sustainability and green manufacturing, risk management and business resilience, decision making in trade and markets, and business management strategies and technology selection, broken down into 11 specific approaches. The review shows that assessing innovation in SMEs requires a multidisciplinary and collaborative approach tailored to business needs. It also shows a preference for fuzzy tools and the combination of different MCDM methods. This article provides an updated diagnosis on the use of multiple criteria in the innovation assessment in SMEs, providing a basis for future research and applications in this field.